(3OQI GdZhGU aj ChgGe GdNhGUs - (3GdbGSe Hf Ydj Hf eMeO Hf YKeGf, CHh eMeO GdMQjQj GdHUQj , J (B516 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg GdPi Ye YHGOg HhXGFa GdYhGQa aEfi QCjJ cKjQkG eef jShG GSeg GdQJH hJSehG HSeII GdGOH aGdaJ gPG GdcJGH JHUQI def fHUQ hJPcQI def GQGO Gf jPcQ hSejJg OQI GdZhGU ai ChgGe GdNhGU s
(3BNQgG (B:s
(3bGd GdTjN GdGeGe GHh eMeO QMeg Gddg agPg ChgGe ai GdgLGA CKHJgG Yf GdYjGf hGdJbWJgG ef cJH LeGYI ef GdGYjGf hai Gddg CSFdge GdJhajb ddebGd GdeJYdb HGdEUGHI ddaYGd GdeLJdH MSf GdGfGHI Gfg HcQeg hdi GdGLGHI s
(3HgG fXGe GdJYbjHIs
(3fSNI Chdis
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B177 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B108s
Keywords: (3GddZIs